A case-control study on Chlamydia psittaci pneumonia and legionella pneumonia - Gao, Ying; Lin, Yuan-jie; Zhang, Wen-long; Ni, Jian-ming; Han, Shu-guang; Bao, Liang (Frontiers in Medicine, 2025)
PurposeAtypical pathogens (Chlamydia psittaci and Legionella) are often detected by metagenomic next-generation sequencing (mNGS). However, the two atypical pneumonias are difficult to distinguish. The aim of this study was to retrospectively analyze the two types of atypical pneumonia and use statistics to find points of differentiation for early diagnosis and timely treatment.MethodsThis retrospective study included all confirmed cases of two types of atypical pneumonia in our institution. The data collected and analyzed included epidemiological, clinical, laboratory, and radiological features.ResultsThe study included 84 patients, 63 with Chlamydia psittaci (C. psittaci) pneumonia, 21 with Legionella pneumonia. (1) Up to 61.9% of patients with C. psittaci pneumonia and Legionella pneumonia had high fevers. More than 90% of patients with Legionella pneumonia had a cough score ≥ 3. Legionella pneumonia patients experienced more severe coughing, chest tightness and shortness of breath symptoms than C. psittaci pneumonia patients (both, p < 0.01). (2) Consolidation, bronchial insufflation, ground-glass opacities, and pleural effusion are the most common chest CT signs of C. psittaci pneumonia and Legionella pneumonia. Legionella pneumonia was more likely to cause ground-glass opacities in the upper left lobe than C. psittaci pneumonia (p = 0.05). There was no statistical difference in other CT findings. (3) C. psittaci pneumonia and Legionella pneumonia were identified by leukocytes, lymphocytes ratio, NLR, blood glucose, cough, chest tightness and shortness of breath. They had AUC’ s of 0.810, 0.709, 0.728, 0.724, 0.795, 0.675, and respective 95% CI’ s of 0.716–0.907, 0.60 5–0.832, 0. 566–0.838, 0.604–0.831, 0.696–0.869, 0.574–0.784; all statistically significant (all P < 0.05; < 0.001, 0.003, 0.008, 0.006, < 0.001, 0.017, respectively). (4) 69.8%, 80.9% of each patients took two or more antibiotics simultaneously before diagnosis, but the difference was not statistically significant (p = 0.32). Some patients received more than four antibiotics, most commonly Legionella pneumonia (23.8%) (p = 0.01).ConclusionClinicians should consider atypical pneumonia, particularly C. psittaci and Legionella pneumonia, when patients present with high fever and chest CT scans showing consolidation accompanied by bronchial insufflation, ground-glass opacities, and pleural effusion. Initially, clinicians can differentiate between the two types of pneumonia based on symptoms (e.g., cough severity, chest tightness and shortness of breath), imaging features (e.g., GGO in the left upper lobe), and laboratory markers (e.g., glucose, leukocytes, NLR, and lymphopenia). This allows for the optimization of antibiotic choices and the reduction of unnecessary multidrug combinations, which can improve prognosis and reduce the risk of drug resistance.